The Impact of Violence on The Main Character in The Novel 00.00 By Ameylia Falensia : Alan Swingewood’s Literary Sociology - Nensilianti, Nensilianti; Ridwan, Ridwan; Wiastra, Wulandari (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2025)
This study aims to analyse the influence of violence on the character development of the main character in the novel 00.00, by Ameylia Falensia using Alan Swengwood’s sociology of literature theory approach. The background of this research is driven by the lack of research that specifically explores the impact of violence from a social perspective in contemporary literary works. Most previous studies focus more on the representation of violence, without exploring how the violence affects the evolution of the main character in the context of social structure, character change, and relationship dynamics. Through this research, it is hoped to bridge the gap by highlighting how violence not only shapes individual identities, but also reflects broader social dynamics in the novel’s narrative. The results of this study are expected to make a new contribution to the study of literary sociology, especially in understanding the impact of violence, through Swengwood’s view of social structure, character change, and relationship dynamics. This research uses a qualitative approach. The type of research used is descriptive research. This analysis uses the theory of literary sociology according to Alan Swingwood. The results show that how the impact of violence is very influential on the main character, which involves social structure, character change, and relationship dynamics in the novel ‘00.00, by Ameylia Falensia. The findings of this study are expected to provide new insights for readers to be more sensitive to issues of violence in society and how to respond to it with solutions that focus on social justice.